Synthesis, characterization and catalytic activity of modified-clays impregnated with Ni for methane reforming - Moronta, Alexander; Iwasa, Nobuhiro; Shimokawabe, Masahide; Fujita, Shin Ichiro; Arai, Masahiko (Ciencia)
One montmorillonite, STx-1 (Texas, USA) was acid activated, aluminum pillared or La-exchanged and then impregnated with Ni. Samples combining these three treatments were also prepared. The synthesized solids were characterized by X-ray diffraction, temperature programmed desorption of cyclohexylamine to evaluate the acidity, temperature programmed oxidation to determine carbon deposits and surface area by N2 adsorption. The catalytic activity was measured using the reforming of methane with CO2. In general low CO2conversions were obtained due to the weak thermal stability of the starting material. Ni/La-pillared and Ni/La-acid-pillared clays showed the highest activity (20 and 25%, respectively) and this was ascribed to the basic properties provided by La addition, which favor the CO2 adsorption. A rapid deactivation of the catalysts was observed and attributed to Ni sintering.